Ontogeny of Carbon Monoxide-Related Gene Expression in a Deep-Diving Marine Mammal - Piotrowski, Elizabeth R.; Tift, Michael S.; Crocker, Daniel E.; Pearson, Anna B.; Vázquez-Medina, José P.; Keith, Anna D.; Khudyakov, Jane I. (Frontiers in Physiology, 2021)
Marine mammals such as northern elephant seals (NES) routinely experience hypoxemia and ischemia-reperfusion events to many tissues during deep dives with no apparent adverse effects. Adaptations to diving include increased antioxidants and elevated oxygen storage capacity associated with high hemoprotein content in blood and muscle. The natural turnover of heme by heme oxygenase enzymes (encoded by HMOX1 and HMOX2) produces endogenous carbon monoxide (CO), which is present at high levels in NES blood and has been shown to have cytoprotective effects in laboratory systems exposed to hypoxia. To understand how pathways associated with endogenous CO production and signaling change across ontogeny in diving mammals, we measured muscle CO and baseline expression of 17 CO-related genes in skeletal muscle and whole blood of three age classes of NES. Muscle CO levels approached those of animals exposed to high exogenous CO, increased with age, and were significantly correlated with gene expression levels. Muscle expression of genes associated with CO production and antioxidant defenses (HMOX1, BVR, GPX3, PRDX1) increased with age and was highest in adult females, while that of genes associated with protection from lipid peroxidation (GPX4, PRDX6, PRDX1, SIRT1) was highest in adult males. In contrast, muscle expression of mitochondrial biogenesis regulators (PGC1A, ESRRA, ESRRG) was highest in pups, while anti-inflammatory genes (HMOX2, NRF2, IL1B) did not vary with age or sex. Blood expression of genes involved in regulation of inflammation (IL1B, NRF2, BVR, IL10) was highest in pups, while HMOX1, HMOX2 and pro-inflammatory markers (TLR4, CCL4, PRDX1, TNFA) did not vary with age. We propose that ontogenetic upregulation of baseline HMOX1 expression in skeletal muscle of NES may, in part, underlie increases in CO levels and expression of genes encoding antioxidant enzymes. HMOX2, in turn, may play a role in regulating inflammation related to ischemia and reperfusion in muscle and circulating immune cells. Our data suggest putative ontogenetic mechanisms that may enable phocid pups to transition to a deep-diving lifestyle, including high baseline expression of genes associated with mitochondrial biogenesis and immune system activation during postnatal development and increased expression of genes associated with protection from lipid peroxidation in adulthood.